PENERAPAN MANAJEMEN PERUBAHAN DENGAN ANALISIS TURNAROUND DALAM MENINGKATKAN KINERJA PERUSAHAAN - HELMALIA HELMALIA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2016)
The theme of the article is financial management. This article discusses how the changes should be made to the Turnaround analysis approach that can improve the performance of a company. The article is the result of the study of literature. Change is an important portion of a management, where every leader is measured ability to predict changes and to make changes as the potential of the company's performance. A leader faces changes by having a vision and strategy that is based on assumptions about the future situation which is expected to occur. Along with the development of science and technology requires a company to change the level of productivity and company performance. This has encouraged management to be able to make changes in various ways or methods. One of them with an analysis of the Turnaround is to do a fundamental change, through changes in leadership, management, operational processes, and changes in the market approach. All these aim to increase the market value and increase the efficiency of the company in the long term. Change does not have to happen, but changes must be able to run well. Management changes are required in order to assist the process of change to become more focused and able to put these changes into the organization or the company's business world.